Interactive Effects of Garlic and Fenugreek on Growth Performance and Serum Biochemical Responses in Awassi Lambs - Baker, Ahmed Gh. (American Journal of Botany and Bioengineering, 2026)
The study was conducted to determine the impact of garlic and fenugreek supplementation on growth performance, as well as the effect of these supplements on the blood biochemical parameters of choice in lambs. Six dietary treatments of three lambs each (completely randomized design, CRD) were used to offer an entire randomized trial to 18 lambs. The treatments were, T1 (control, no additives), T2 (1g garlic), T3 (2g garlic), T4 (1g fenugreek), T5 (2g fenugreek), and T6 (1g garlic + 1g fenugreek) and given one capsule every animal trial was conducted for a period of 60 days, beginning in April. Body-weight characteristics such as initial weight and final weight and change in weight were measured. The measurements of blood biochemical parameters were also performed, including triglycerides (TG), total cholesterol (Ch), low-density lipoprotein (LDL), high-density lipoprotein (HDL), albumin (Alb), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and chloride (ChL). One-way ANOVA under CRD was used to analyse the data and compare the results of the means of treatment using the multiple range test at P=0.05 as postulated by Duncan. Findings showed that dietary treatments had significant effects on initial body weight (P ⁻ 0.05), final body weight (P ⁻ 0.01), and also weight gain (P ⁘ 0.01). Fenugreek (T4) and combined supplementation (T6) groups of lambs recorded the highest final body weights. There were found no substantial differences between treatments in the parameters of lipid profiles (TG, Ch, LDL, and HDL) and liver enzyme activities (ALT and AST) (P 0.05). Significant differences however existed in chloride levels (P ≤ 0.05) and the combined treatment had lower chloride levels than most of the other treatments. Conclusively, the growth performance of lambs was increased by supplementing with garlic and fenugreek, especially when used in combination with each other, and there were no adverse effects of most blood biochemical parameters and this implies that the supplements of garlic and fenugreek may be used safely as natural feed additives in lamb production.